Impacts of gait biomechanics of patients with thoracolumbar kyphosis secondary to Scheuermann’s disease - Cheng, Hao; Jiang, Zi-Ang; Chen, Liang; Wang, Guo-Dong; Liu, Xiao-Yang; Sun, Jian-Min; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Thoracolumbar kyphosis (TLK) is a common feature in patients with spinal deformities. However, due to limited studies, the effects of TLK on gait have not been reported. The objective of the study was to quantify the impacts of TLK on gait parameters. We recruited 20 patients of Scheuermann’s disease with TLK (mean age=24.1±3.5) and 20 asymptomatic subjects (mean age=24.5±3.5). The gait motion analysis was conducted. The stride length was shorter in the TLK group compared to control group (1.24±0.11m vs. 1.36±0.21m, P =0.04). Compared to control group, the stride time and step time were more prolonged in the TLK group (1.18±0.11s vs1.11±0.08s, p=0.03; 0.59±0.06s vs. 0.56±0.04s, p=0.04). The gait speed of the TLK group was significantly slower than it of control group (1.05±0.12 m/s vs1.17±0.14m/s, P =0.01); In the sagittal plane, the range of motion (ROM) of the hip in the TLK group was significantly smaller than the control group (37.71±4.35o vs. 40.05±3.71 o, P =0.00). In the transverse plane, the adduction/abduction ROMs of the knee and ankle, as well as the internal and external rotation of the knee, were smaller in TLK group than ROMs in the control group (4.66±2.21o vs. 5.61±1.82o, P=0.00; 11.48±3.97o vs. 13.16±5.6o, P=0.02; 9.00±5.14o vs12.95±5.78o, P=0.00). The present study find that compared with the asymptomatic group, TLK decreases the values of several gait parameters and these impacts have the potential to exacerbate degenerative progress of joints in the lower extremities. These abnormal features of gait can also serve as a guideline for physicians to focus on TLK in these patients.